Young Hip: an exploration into young patients’ (aged > 50 years) expectations following primary total hip arthroplasty: a qualitative study - Louise E Mew; Vanessa Heaslip; Tikki Immins; Thomas W Wainwright (Bone & Joint Open)
Aims: Total hip arthroplasties (THAs) are common operations performed in orthopaedics. Though initially developed to address hip conditions in older patients, demand in younger patients is increasing. Research in older populations informs current practice, and it is unclear if outcome priorities are the same in younger patients. The study’s aim was to explore the expectations and priorities of younger patients’ (aged < 50 years) undergoing THA. Methods: Using interpretive phenomenological analysis (IPA) methodology, ten patients were recruited from one UK hospital. Semistructured interviews occurred at three timepoints (pre-surgery, six weeks, and six months post-surgery). This study has been reported using the COnsolidated criteria for REporting Qualitative research (COREQ). Results: Six themes were identified: ‘I’m just constantly in pain’, ‘Giving up hope’, ‘Living a process that does not reflect me’, ‘This is not who I’m meant to be’, ‘My family didn’t sign up for this’, and ‘I can’t do anything’. Some themes were independent of patient age, such as pain, and experiences of healthcare. However, other findings may be more imperative to the younger patient than the older patient. Conclusion: The Young Hip study highlighted aspects currently overlooked in younger THA patients. Participants were aware that they were not the accepted patient profile for THA, and expressed having to fight to be heard. Function was considered in terms of responsibilities and roles in society, rather than traditional clinical perceptions of mobility. The findings demonstrated that current care pathways are not fully addressing the needs of younger THA patients. Further development of a personalized THA pathway, allowing for more focus on person-centred care, could address issues raised by this study, more effectively supporting younger patients. Cite this article: Bone Jt Open 2025;6(7):807–815.